The impact of studying abroad on students’ intercultural competence: An interview study - Sobkowiak, Paweł (Studies in Second Language Learning and Teaching, 2019)
This paper presents qualitative research examining to what extent sojourns abroad engage their participants in intercultural interactions and whether or not such experience translates into students’ intercultural growth. The results of the study demonstrated that studying abroad did not provide students with ample opportunities to immerse into the local community and fully discover a new cultural environment. However, students surrounded by local and their fellow international students met foreign cultures, which motivated them to explore and interpret the encountered diversity, and thus equipped them with knowledge about foreign cultures, sensitizing them to cultural diversity. Sometimes such contacts challenged students’ preconceived judgments and stereotypes of specific cultural groups, their ways of thinking, valuing and acting, and resulted, to a lesser or greater extent, in rethinking these, leading to changing attitudes and values. International experiences also stimulated students to self-analyze their own cultural identity, and thereby contributed to their growth in self-awareness in this respect. By offering opportunities for experiencing cultural differences and prompting students to develop coping strategies and to make references to the home culture, the sojourn is thus of significant importance for tertiary students, allowing for fostering their intercultural development to a certain degree.